PENGUKURAN STRES KERJA DAN BEBAN KERJA MENTAL BERDASARKAN SHIFT KERJA MENGGUNAKAN METODE NASA-TASK LOAD INDEKS (TLX) DAN DESCRIPTIVE ANALYTIC - Simanjuntak, Risma Adelina; Yusuf, Muhammad; Jeva Setty, Esterani (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2022)
WL Alumunium is a company engaged in the manufacture of household appliances in the Yogyakarta Special Region. WL Aluminum produces various types of products, including pans, kettles, citel sticks and pans. The company has two work shifts, namely in the morning 07.00 - 11.30 and noon at 12.30 - 16.00 WIB. The majority of workers are male and the research is carried out specifically in the production section. In this study, 2 (two) methods were used, namely NASA-task load index (TLX) and descriptive analytic. The NASA-TLX method is used to calculate the workload and work stress felt by employees through the calculation of six indicators, namely physical needs, mental needs, performance, effort, stress levels and time requirements, and descriptive analysis is used to describe the subject and describe workload and work stress. that happened. The purpose of this method is to determine the workload and work stress of employees based on each work shift. The results of the study using NASA-TLX showed that the workload for both shifts was in the high category, namely between the score of 50-79, but for the work stress indicator it was the lowest level of the six NASA-TLX indicators, so that even though the workload in the current condition was high, workers could still survive with work activities because they are accustomed to existing work activities. Through descriptive analytic, it can be seen that the biggest workload felt by employees for each work shift is physical needs. It can be seen that employees aged 50 and over tire more quickly because the decrease in physical energy during work activities is faster than younger employees.